IMPLIKASI KEGIATAN PROGRAM DOSEN KE SEKOLAH (PDS) DI PERKULIAHAN PENDIDIKAN EKONOMI FKIP UNIVERSITAS SRIWIJAYA - Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2019)
Abstract Learning activities carried out in educational research statistics courses in the FKIP Sriwijaya University economic education study program are an extension of the lecturer assignment program to schools (PDS) in 2018/2019. The learning model used in educational research statistics courses is in accordance with the 2013 curriculum guidelines, namely the discovery learning, inquiry, Problem Based Learning and Project Based Learning methods. The learning models are applied for 8 times face to face with details of 2 times face to face applying the learning model of discovery learning; 2 second face-to-face approaches to inquiry learning; 2 times the third face to face applying the learning model of problem based learning; 2 times face to face applying discovery learning learning model; 2 times the fourth face to face applying the project based learning model. The PDS program in higher education has a positive impact on prospective teacher students to be able to understand more deeply about the learning situation that occurs in schools, ranging from the need for continuous motivation to students from the beginning of learning to closing learning in the form of giving reinforcement.Key words: Lecturer to School Program, Economic Education Lectures AbstrakKegiatan pembelajaran yang dilakukan pada mata kuliah statistik penelitian pendidikan di program studi pendidikan ekonomi FKIP Universitas Sriwijaya merupakan pengimbasan program penugasan dosen ke sekolah (PDS) di tahun 2018/2019. Model pembelajaran yang di gunakan pada mata kuliah statistik penelitian pendidikan sesuai dengan tuntunan kurikulum 2013 yaitu metode pembelajaran discovery learning, inkuiri, Problem Based Learning dan Project Based Learning. Model-model pembelajaran tersebut diterapkan selama 8 kali tatap muka dengan rincian 2 kali tatap muka menerapkan model pembelajaran discovery learning; 2 kali tatap muka kedua menerapkan model pembelajaran inquiry learning; 2 kali tatap muka ke tiga menerapkan model pembelajaran problem based learning; 2 kali tatap muka menerapkan model pembelajaran discovery learning; 2 kali tatap muka ke empat menerapkan model pembelajaran project based learning. Program PDS di perguruan tinggi memberikan dampak yang positif kepada mahasiswa calon guru untuk dapat memahami lebih mendalam tentang situasi pembelajaran yang terjadi di sekolah, mulai dari perlunya pemberian motivasi secara terus menerus kepada siswa mulai dari awal pembelajaran sampai menutup pembelajaran berupa pemberian penguatan-penguatan Kata-kata kunci : Program Dosen ke Sekolah, Perkuliahan Pendidikan Ekonomi